2019
DOI: 10.3390/cells8060515
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment Biomarkers of Anti-Tumour Necrosis Factor Therapy Response in Crohn’s Disease—A Systematic Review and Gene Ontology Analysis

Abstract: The most prominent treatment for the serious cases of Crohn’s disease (CD) are biological tumour necrosis factor (TNF) inhibitors. Unfortunately, therapy nonresponse is still a serious issue in ~1/3 of CD patients. Accurate prediction of responsiveness prior to therapy start would therefore be of great value. Clinical predictors have, however, proved insufficient. Here, we integrate genomic and expression data on potential pre-treatment biomarkers of anti-TNF nonresponse. We show that there is almost no overla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 86 publications
(112 reference statements)
0
18
0
Order By: Relevance
“…Anti-TNF therapy is of pivotal importance in patients with CD and genomic biomarkers that would tailor personalized treatment are currently needed, in particular as new biologicals for CD treatment have recently emerged. In the recent systematic review of anti-TNF genomic biomarkers in CD, it was noted that almost no candidate gene could be confirmed in an independent association study and no overlap was detected among genes identified with association and gene expression studies 18 . In the present study, we have adopted a new approach 19 for the integration of PBMCs derived transcriptomic and genomic data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-TNF therapy is of pivotal importance in patients with CD and genomic biomarkers that would tailor personalized treatment are currently needed, in particular as new biologicals for CD treatment have recently emerged. In the recent systematic review of anti-TNF genomic biomarkers in CD, it was noted that almost no candidate gene could be confirmed in an independent association study and no overlap was detected among genes identified with association and gene expression studies 18 . In the present study, we have adopted a new approach 19 for the integration of PBMCs derived transcriptomic and genomic data.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on genetic background and gene expression 11 17 as potential biomarkers for anti-TNF treatment response. Currently the genomics markers of anti-TNF response in CD are not reaching significant thresholds and practically no reproducibility between genetic and expression markers exists, as identified by the first integration of genomic and expression data prior to anti-TNF treatment in a systematic review 18 . Prediction profiles have been mostly identified using epithelial gene expression data for which colonoscopy and biopsy sampling are needed 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical manifestations can be used to predict side effects may be inadvertently ignored by physicians. The genetic expressiom markers were studied for prediction of TNF antagonists induced psoriasis [53]. Some studies suggested that suspending the use of biological agents or extending the duration of drug therapy has no effect on the relief of drug-induced psoriasis [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…This approach identifies molecular functions, cellular components, biological processes, and biochemical pathways related to the studied genes. 10 Physical and chemical properties of genes and their regulatory effects on each other provide useful information to screen and rank a set of genes to find the crucial ones. Activation, inhibition, catalysis, binding, reaction, and post-translation modification actions can be determined when an action map is plotted.…”
Section: Introductionmentioning
confidence: 99%